Long‐ and short‐term inpatients with schizophrenia in China: Implications for community‐based service development. (7th September 2012) - Wu, Guowei; Ouyang, Xuan; Yang, Bo; Li, Li; Wang, Zheng; Yi, Wenying; Liu, Chang; Wang, Peng; Chiu, Helen F.K.; Lee, Edwin; Xue, Zhimin; Rosenheck, Robert; et al.
Abstract: Introduction: There is an increasing interest in the patterns of mental health care of people with serious mental illnesses in China, where outpatient and community‐based care are not fully developed and long‐term hospitalization is still not uncommon. Comparison of sociodemographic and clinical characteristics of long‐term and short‐term inpatients diagnosed with schizophrenia can be informative about pattern of treatment and their relationship to services needs. Methods: Seventy‐three long‐term schizophrenia inpatients (current length of stay of more than 5 years) were compared to 116 short‐term schizophrenia inpatients (current length of stay of 30 days or less) assessed with the Individual Background Questionnaire, the Positive and Negative Syndrome Scale (PANSS) and the Social Support Rating Scale (SSRS). Results: There was no significant difference between the groups on the total PANSS symptom score but the short‐term inpatients scored significantly higher than their long‐term counterparts on the Positive Syndrome sub‐scale and the SSRS and lower on the Negative Syndrome sub‐scale. Discussion: Differences in symptomatology and social functioning may be related to better medication adherence and more extended social isolation among long‐term inpatients while the increased positive symptoms are likely to reflect more acute disease process in short‐term inpatients, and possibly poorer medication adherence. These differences may be especially pronounced in developing countries like China in which community‐based services need to be more fully developed to facilitate medication adherence and prevent relapse, and to support community adjustment of socially isolated patients who otherwise require hospitalization.